Exploring Clec9a in dendritic cell-based tumor immunotherapy for molecular insights and therapeutic potentials - Zubair Hussain; Yueteng Zhang; Lu Qiu; Shanshan Gou; Kangdong Liu (npj Vaccines)
Abstract The pivotal role of type 1 conventional dendritic cells (cDC1s) in the field of dendritic cell (DC)-based tumor immunotherapies has been gaining increasing recognition due to their superior antigen cross-presentation abilities and essential role in modulating immune responses. This review specifically highlights the C-type lectin receptor family 9 member A (Clec9a or DNGR-1), which is exclusively expressed on cDC1s and plays a pivotal role in augmenting antigen cross-presentation and cytotoxic T lymphocyte (CTL) responses while simultaneously mitigating off-target effects. These effects include the enhancement of the cDC1s cross-presentation, reducing autoimmune responses and systemic inflammation, as well as preventing the non-specific activation of other immune cells. Consequently, these actions may contribute to reduced toxicity and enhanced treatment efficacy in immunotherapy. The exceptional ability of Clec9a to cross-present dead cell-associated antigens and enhance both humoral and CTL responses makes it an optimal receptor for DC-based strategies aimed at strengthening antitumor immunity. This review provides a comprehensive overview of the molecular characterization, expression, and signaling mechanisms of Clec9a. Furthermore, it discusses the role of Clec9a in the induction and functional activation of Clec9a+ cDC1s, with a particular focus on addressing the challenges related to off-target effects and immune tolerance in the development of tumor vaccines. Additionally, this review explores the potential of Clec9a-targeted approaches to enhance the immunogenicity of tumor vaccines and addresses the utilization of Clec9a as a delivery target for specific agonists (such as STING agonists and αGC) to enhance their therapeutic effects. This novel approach leverages Clec9a’s capacity to improve the precision and efficacy of these immunomodulatory molecules in tumor treatment. In summary, this review presents compelling evidence positioning Clec9a as a promising target for DC-based tumor immunotherapy, capable of enhancing the efficacy of vaccines and immune responses while minimizing adverse effects.